FEATURES OF METHODOLOGIES OF THESIS IN MEDICINE - O. V. Osetrova (Вестник трансплантологии и искусственных органов, 2014)
The structure of methodologies of the dissertation research (thesis) is given. Disclosure of the main structural elements in presenting the general characteristics of the study: the title of the dissertation; aim and relevance of the study; contradiction and problem statement; object and subject of the study; aim and hypothesis; novelty, theoretical and practical importance; provisions for the defense. The features of the formation of methodologies for medical research are shown. Tests to practice in formulating some methodological concepts are proposed. The content of the material presented can serve as a methodological guideline for scientifi c researchers to adjust basic ideas, refl ecting the main concepts and relationship between them in a generalized form.